2005
DOI: 10.1080/02692170500213319
|View full text |Cite
|
Sign up to set email alerts
|

Financial Globalization, Social Exclusion and Financial Crisis

Abstract: This paper suggests one set of mechanisms that ties financial globalization processes to local dynamics of financial inclusion or exclusion. Specifically, this paper explores the worldwide reconsideration of financial firms' strategies that has accompanied financial globalization. It is shown that the neoliberal and asymmetric-information approaches to credit markets and financial crises in developing economies overlook these dimensions of financial globalization because of their tendency to focus on represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 18 publications
0
42
0
5
Order By: Relevance
“…They are either viewed as not bankable or creditworthy [8]. Therefore, the banks charge high interests in order to discriminate among; and have enough cover on their transaction with this group of borrowers [9], [10]. The moral hazard problem the lenders face is a reflection of their susceptibility to adverse selection of potential clients.…”
Section: A Theory Of Imperfect Marketmentioning
confidence: 99%
“…They are either viewed as not bankable or creditworthy [8]. Therefore, the banks charge high interests in order to discriminate among; and have enough cover on their transaction with this group of borrowers [9], [10]. The moral hazard problem the lenders face is a reflection of their susceptibility to adverse selection of potential clients.…”
Section: A Theory Of Imperfect Marketmentioning
confidence: 99%
“…First coined in the mid-1990s by Leyshon and Thrift (1995), the idea has been picked and revived by Dymski (Dymski 2005;Dymski and Li 2003) as a measure of engagement with the financial system, so that the possession of financial citizenship confers on individuals and households the right and ability to participate fully in the economy and to accumulate wealth. This is significant because, as part of the broader process of neoliberalization (Peck and Tickell 2002), the contract between the individual and the state is being remade, with personal responsibility and financial markets becoming the default route for short-term income smoothing and long-term financial security.…”
Section: Spacing Financializationmentioning
confidence: 99%
“…timorexpress.com/flores-raya/lima-koperasi-dinilailintah-darat; http://www.lensaindonesia.com/2015/06/ 06/rentenir-merajalela-bupati-bogor-malah-tutupmata.html; http://finansial.bisnis.com/read/20150611/ 89/442504/suku-bunga-lkm-10-tahun-ke-depanpraktik-rentenir-berkurang; http://petahmelayu.com/kacau-banyak-lintah-daratberkedok-koperasi.html; http://www.hidayatullah.com/berita/nasional/read/20 15/02/03/38026/ulah-lintah-darat-pinjam-6-juta-bayar-40-juta.html; http://www.kapurnews.com/2015/05/28/ waspada-banyak-lintah-darat-berkedok-koperasi-dimeranti 13 foreign bank is defined as a bank with more than 51% of shares owned by foreign parties. The above argument gains strong support from Dymski (2005) and Hamada (2013). Dymski (2005) found that financial globalization created financial exclusion, which was caused by multinational financial corporate strategies focused on the most profitable credit markets.…”
Section: May 152mentioning
confidence: 86%
“…The above argument gains strong support from Dymski (2005) and Hamada (2013). Dymski (2005) found that financial globalization created financial exclusion, which was caused by multinational financial corporate strategies focused on the most profitable credit markets. Hamada (2013) subsequently provided evidence that the foreign owned banks in Indonesia tended to reduce their credit to Small and Medium Enterprises (SMEs).…”
Section: May 152mentioning
confidence: 86%